An investigation into the legitimacy of xenotransplantation - Abdolreza Farhadian (مطالعات فقه و حقوق اسلامی)
Xenotransplantation, or implantation of animal organs into human bodies, is one of the recent significant advances in medical sciences. This study uses a descriptive-analytical design to examine the legitimacy of this phenomenon in light of Fiqh and Iranian legal system. The results indicate that adopting a traditional approach may prevent decreeing a permission for this phenomenon. However, taking an intentional approach to Fiqh enables going beyond traditional approaches and consequently decree a permission. The legitimacy of the xenotransplantation phenomenon can be justified in light of important principles such as the principle of correctness, the no-harm rule, and the principle of self-preservation and healing. There is no evidence in Fiqh forbidding xenotransplantation; thus, everyone is supposed to save themselves from harm and attempt to cure possible diseases. Defects in any organs of the human body could be considered as a clear example of a disease, thus justifying the process of xenotransplantation for curing a disease.